2021
DOI: 10.1002/eat.23527
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating disorders of gut‐brain interaction in eating disorders

Abstract: Objective Eating disorders commonly co‐occur with gastrointestinal problems. This case–control study aimed to (a) document the prevalence of disorders of gut‐brain interaction (DGBI) in eating disorders, (b) examine the specific impact of disordered eating behaviors on the risk of DGBI, and (c) explore the impact of current eating disorder psychopathology on DGBI. Method We included 765 cases with eating disorders and 1,240 controls. DGBI were assessed via the ROME III questionnaire. Prevalences of DGBI were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…In clinical settings, patients with AN commonly report gastrointestinal complaints such as exaggerated fullness in response to small meals (i.e., postprandial fullness), early satiety, and abdominal pain [39 •]. They also report bowel and bladder symptoms outside of mealtimes, such as fullness, bloating, and constipation [40][41][42], and frequently exhibit gastrointestinal disorders [43] as well as functional gastrointestinal disorders [44]. The physiology underlying these abnormal perceptions has not been examined extensively in laboratory settings.…”
Section: Current Evidence Of Gastrointestinal Dysfunction In Eating Disordersmentioning
confidence: 99%
“…In clinical settings, patients with AN commonly report gastrointestinal complaints such as exaggerated fullness in response to small meals (i.e., postprandial fullness), early satiety, and abdominal pain [39 •]. They also report bowel and bladder symptoms outside of mealtimes, such as fullness, bloating, and constipation [40][41][42], and frequently exhibit gastrointestinal disorders [43] as well as functional gastrointestinal disorders [44]. The physiology underlying these abnormal perceptions has not been examined extensively in laboratory settings.…”
Section: Current Evidence Of Gastrointestinal Dysfunction In Eating Disordersmentioning
confidence: 99%
“…13 The presence of at least one DGBI in individuals with ED has been shown to be as high as 95.5%. 14 Diagnosis of ARFID has been reported to occur frequently in patients with gastroparesis 15 and inflammatory bowel disease, 16 and ARFID symptoms are often related to fear of gastrointestinal symptoms in patients with DGBI. 17 Recent studies investigating ARFID in irritable bowel syndrome (IBS) have shown those with severe food avoidance and restriction have more severe symptoms overall, reduced quality of life and reduced nutrient intake.…”
Section: Introductionmentioning
confidence: 99%
“…• Case-control study showed 88.2% of people with anorexia and 94.7% of people with bulimia had at least one DGBI14 …”
mentioning
confidence: 99%
“…These results demonstrate treatment barriers created by discrepancies between how service is provided in a Westernized medical system and the cultural presentations of a condition, highlighting the importance of culturally responsive research and noting limitations in research generalizability (Ma et al, in press; Simons, Shoda, & Lindsay, 2017). In addition, EDs commonly co‐occur with problems in the gastrointestinal system and the communications along the gut‐brain axis may have important implications in ED research (Hooks, Konsman, & O'Malley, 2019; Murray et al, 2020; Wiklund, Rania, Kuja‐Halkola, Thornton, & Bulik, 2021). It is also possible that the participants experienced both gastrointestinal and disordered eating symptoms but sought treatment for the gastrointestinal problems because it is more culturally sanctioned to report an illness traditionally classified as physical versus mental.…”
Section: Discussionmentioning
confidence: 99%